The Significance of Qirā̄ʼāt as a Source of Quranic Interpretation | أهمية القراءات كمصدر للمفسر وكيفية التعامل معها - Ahmad Kusyairi Suhail (Al-Zahra : Journal for Islamic and Arabic Studies, 2009)
this article talks about qiraat as a source of interpreting the quran. the writer emphasizes that a quranic interpreter has to understand knowledge of qiraat. by knowing of qiraat, the interpreter can understand better and properly. in some cases an interpreter could deeply understand on one verse categories; the valid and invalid qiraat. and explores about how a quranis interpreter deals with that knowledge as a source of interpreting of the quran.